Acute Pontine Ischemic Stroke in a Healthy Child With Intracranial Vasculopathy. (November 2019) - Kousa, Youssef A.; Murnick, Jonathan; Burton, Justin; DiSabella, Marc; Pergami, Paola
Here we report the case of a previously healthy 8-year-old boy who presented with altered mental status, right facial droop and right-sided hemiplegia the day after playing in an inflatable bouncer. No head trauma was reported by the patient nor witnessed by the parents. Urgent magnetic resonance imaging (MRI) demonstrated acute ischemic infarction in the left pons; computed tomographic angiography excluded arterial dissection but identified a small hyperdense filling defect in the basilar artery, later confirmed to be a calcification at the origin of a perforating artery. Pediatric National Institutes of Health (PedNIH) Stroke Scale score was 15. Infectious, inflammatory, hypercoagulable and additional vascular causes were excluded. Although the cause of the calcification remains obscure, we speculate that, similarly to mineralizing microangiopathy, a minor trauma led to stroke in this child. To our knowledge, mineralizing microangiopathy, the well-described entity affecting perforating arteries of the anterior circulation in young children leading to basal ganglia stroke following minor head traumas has not been described in the posterior circulation or in previously healthy school-age children.